2007
DOI: 10.1213/01.ane.0000287676.39323.9e
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Femoral Nerve Blockade Administered Preclinically for Pain Relief in Femoral Trauma

Abstract: Preclinically administered femoral nerve blockade effectively decreases pain, anxiety, and heart rate after femoral trauma. Regional blockade is an option for out-of-hospital analgesia administered by a trained physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 9 publications
2
47
0
6
Order By: Relevance
“…It is possible that their high compliance levels can be explained by intensive pre-trial training (the intensive care paramedics required a 16-hour training programme before acceptance onto the trial) and better comprehension of the necessity for a robust, well-conducted study. 37,143 Those trials involving fluid administration, including four of the head-injury trials, to which paramedics were blinded (using identical, randomised fluid bags) and therefore had no control over which interventions they were giving, had compliance levels of over 90%. 139,141 In these cases the paramedics were unaware of which treatments they were administering and were therefore unable to decide to break treatment protocol.…”
Section: Compliancementioning
confidence: 99%
“…It is possible that their high compliance levels can be explained by intensive pre-trial training (the intensive care paramedics required a 16-hour training programme before acceptance onto the trial) and better comprehension of the necessity for a robust, well-conducted study. 37,143 Those trials involving fluid administration, including four of the head-injury trials, to which paramedics were blinded (using identical, randomised fluid bags) and therefore had no control over which interventions they were giving, had compliance levels of over 90%. 139,141 In these cases the paramedics were unaware of which treatments they were administering and were therefore unable to decide to break treatment protocol.…”
Section: Compliancementioning
confidence: 99%
“…There is sufficient data to show the usefulness of FNB to relieve pain from fracture of the femur and now, is being used for positioning during central neuraxial blockade as well. 3,4,12,[19][20][21][22] Femoral nerve block can be performed using peripheral nerve stimulator, ultrasound guided technique or by loss of resistance technique. Geier KO concluded that there were no significant differences regarding efficiency between loss of resistance and peripheral nerve stimulator methods.…”
mentioning
confidence: 99%
“…13 The use of femoral nerve block to relieve pain is now frequently being used during spinal anathesia. [17][18][19] In our study, we found the femoral nerve blocker, lignocaine to be significantly better than fentanyl for the positioning of the hip for surgery with the VAS scores being significantly lower. This was found to be in accordance in other similar studies.…”
Section: Discussionmentioning
confidence: 51%